Imaging Predictors of Improvement From a Motor Learning–Based Intervention for Children With Unilateral Cerebral Palsy. (August 2016) - Schertz, Mitchell; Shiran, Shelly I.; Myers, Vicki; Weinstein, Maya; Fattal-Valevski, Aviva; Artzi, Moran; Ben Bashat, Dafna; Gordon, Andrew M.; Green, Dido
Background . Motor-learning interventions may improve hand function in children with unilateral cerebral palsy (UCP) but with inconsistent outcomes across participants. Objective . To examine if pre-intervention brain imaging predicts benefit from bimanual intervention. Method . Twenty children with UCP with Manual Ability Classification System levels I to III, aged 7-16 years, participated in an intensive bimanual intervention. Assessments included the Assisting Hand Assessment (AHA), Jebsen Taylor Test of Hand Function (JTTHF) and Children's Hand Experience Questionnaire (CHEQ) at baseline (T1), completion (T2) and 8-10 weeks post-intervention (T3). Imaging at baseline included conventional structural (radiological score), functional (fMRI) and diffusion tensor imaging (DTI). Results . Improvements were seen across assessments; AHA ( P = 0.04), JTTHF ( P < .001) and CHEQ ( P < 0.001). Radiological score significantly correlated with improvement at T2; AHA ( r = .475) and CHEQ ( r = .632), but negatively with improvement on unimanual measures at T3 (JTTFH r = −.514). fMRI showed negative correlations between contralesional brain activation when moving the affected hand and AHA improvements (T2: r = −.562, T3: r = −0.479). Fractional Anisotropy in the affected posterior limb of the internal capsule correlated negatively with increased bimanual use on CHEQ at T2 ( r = −547) and AHA at T3 ( r = −.656). Conclusions . Children with greater structural, functional and connective brain damage showed enhanced responses to bimanual intervention. Baseline imaging may identify parameters predicting response to intervention in children with UCP.